Kajian Ketahanan Batuan Clay Shale Formasi Jatiluhur di Sentul City Jawa Barat - Revia Oktaviani; Paulus P Raharjo; Imam A Sadisun (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2018)
The mechanical properties of Clay Shale are very unique. When it is dry, it shrinks and hardens, butwhen it absorbs water, it swells and to some extent loses its shear strength so that the drop-instrength can occur suddenly even with its own weight. Due to the nature of the swell-shrink that arestrongly influenced by climate and weather, clay shale durability may decrease over time when indirect contact with air and water. Research on clay shale was done in Sentul City, Bogor - West Java,Indonesia on Jatiluhur formation, using dynamic slaking (slake durability test) and slaking static test.Dynamic slacking test is done in three times i.e. after sampling, after 3 months and after 9 months.Slake durability test results from 3 different drilling points, shows that within 9 months, has not seenthe decreasing effect of durability. With a low Plasticity index, the durability research in Sentul City isin medium durability to medium-high durability classification.